Cerebral Ultrasound at Term-Equivalent Age: Correlations with Neuro-Motor Outcomes at 12–24 Months Corrected Age - Adrian Ioan Toma; Vlad Dima; Lidia Rusu; Alexandra Floriana Nemeș; Bogdan Florin Gonț; Alexandra Arghirescu; Andreea Necula; Alina Fieraru; Roxana Stoiciu; Larisa Andrășoaie; Loredana Mitran; Claudia Mehedințu; et al. (Children)
Background/Objectives: Our research aimed to assess if correlations could be found between items evaluated at the cerebral ultrasound performed at term-equivalent age (TEA) and neuro-motor outcomes evaluated at 12 and 24 months of corrected age in a group of preterm infants. Methods: The following were assessed: the Levine Index, the diagonals of the lateral ventricles, the size of the ventricular midbody, the sinocortical distance, the width of the basal ganglia, the cortical depth at the level of the cingular sulcus and the maturation of the gyral folding. The neurologic evaluation was performed at 12 and 24 months of corrected age, according to the Amiel Tison neurologic examination, and the items from the calendar of motor acquisitions were used as outcome measures of the study—gross and fine motor subsets. The comparisons between the different groups were performed using the FANOVA test, with a statistically significant association for a p < 0.05. Results: The abnormal gross motor acquisitions at 12 months were significantly associated with an increased size of the ventricular midbody (p < 0.009) and a significantly decreased diameter of the basal ganglia (p < 0.011) on the TEA cerebral ultrasound. At 24 months, a significant association was found with increased size of the ventricular midbody (>10.33 mm) (p < 0.001), a decreased diameter of the basal ganglia (<12.9 mm) (p < 0.016), a decreased cortical depth (p < 0.021) and an immature gyral maturation pattern (p < 0.001). In the case of severely abnormal fine motor outcomes, at 12 months, there were statistically significant associations with an increased size of the ventricular midbody (p < 0.001) and an immature gyral folding pattern (p < 0.0180); at 24 months, significant associations were noted with the size of ventricular midbody (p < 0.001), a decreased diameter of the basal ganglia (p < 0.016), a decreased cortical depth (p < 0.021) and an immature gyration folding (p < 0.001). Conclusions: The abnormal gross and fine motor outcome in former premature infants at 12–24 months corrected age is significantly associated with abnormal findings in the head ultrasound examination performed at TEA reflecting both white matter (increased midbody distance) and grey matter (decreased diameter of the basal ganglia, decreased cortical depth and an immature gyration pattern) involvement.